ANALISIS FAKTOR RISIKO STROKE PADA PASIEN STROKE RAWAT INAP DI RSUD BANJARBARU - Agianto; Manurung, Minarti; Diani, Noor (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Stroke is a major causes of disability in the world and the main cause of death in Indonesia, so theprevention is very important to minimize the incidence of stroke. The appropriateness of strokeprevention isto control the risk factors of stroke. The purpose of this study was to analyze therelationship between risk factors and the incidence of stroke in Banjarbaru’s Hospital in 2014. Thisstudy used a descriptive analytic observational study design with case-control approach. The subjectswere 84 stroke patients (42 case group and 42 control group), consecutive sampling techniqe wasused and the tool was questionnaire. Dataanalysis used univariate and bivariate statistics. Theresultswere, for risk factor that unmodifiable was family history with p value 0.016 (OR = 3.281). Formodifiable risk factors were the total cholesterol (0.000; OR = 5.638), hypertension (0.001; OR =5.392) and LDL (0.002, OR = 8.000).